Synthesis and Reactivity of the Phosphorus Analogues of Cyclopentadienone, Tricyclopentanone, and Housene. (12th January 2018) - Krachko, Tetiana; Ehlers, Andreas W.; Nieger, Martin; Lutz, Martin; Slootweg, J. Chris
Abstract: The phosphorus analogues of cyclopentadienone, tricyclopentanone, and housene were accessed from bis(cyclopropenyl)diphosphetanedione3, which was prepared by mixing 1, 2, 3‐tris‐tert‐butylcyclopropenium tetrafluoroborate (1 ) and sodium phosphaethynolate [Na(OCP)(dioxane)n ]. While photolysis of3 results in decarbonylation, yielding bis(cyclopropenyl)diphosphene4 and after rearrangement diphosphahousene5, thermolysis of3 leads to phosphatricyclo[2.1.0.0]pentanone7 . Metal‐mediated valence isomerization of7 and subsequent demetalation provides access to phosphacyclopentadienone12 .